Pengaruh Jumlah Uang Beredar, Inflasi, Suku Bunga Riil, dan Nilai Tukar terhadap Pertumbuhan Ekonomi di Negara ASEAN Periode 2019–2023 - Muhammad Syahidin; Firdaus Budhy Saputro (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
This study examines the impact of monetary variables, namely money supply, inflation, real interest rate, and exchange rate, on economic growth in ASEAN countries during 2019–2023. The sample consists of five ASEAN countries Indonesia, Malaysia, Thailand, the Philippines, and Vietnam (ASEAN-5) selected through purposive sampling based on data availability. The study employs annual panel data covering five years with a total of 25 balanced observations. The analysis is conducted using panel regression with the Random Effect Model (REM) estimated through the Panel EGLS approach. The results indicate that, jointly, money supply, inflation, real interest rate, and exchange rate have no significant effect on economic growth. However, the partial test reveals that inflation has a positive and significant effect on economic growth, while money supply and real interest rate show positive but insignificant effects. The exchange rate demonstrates a negative but insignificant relationship with economic growth. These findings suggest that during the post-pandemic recovery period, inflation becomes the most influential monetary factor explaining economic growth variation in ASEAN-5, whereas other monetary variables do not strongly affect real output in the short run. Policy implications highlight the importance of maintaining inflation stability, strengthening monetary transmission to the real sector, and improving macroeconomic stability to support sustainable economic growth.